Effect of Ferulic Acid on High-Carbohydrate, High-Fat Diet-Induced Metabolic Syndrome in Rats - Senaphan, Ketmanee; Boonla, Orachorn; Kukongviriyapan, Upa; Timinkul, Aomkhan; Pakdeechote, Poungrat; Kukongviriyapan, Veerapol; Pannangpetch, Patchareewan; Prachaney, Parichat (Srinagarind Medical Journal, 2013)
Background and objective: Metabolic syndrome (MS) is the presence of multiple risk factors for diabetes and cardiovascular disease, including obesity, hyperglycemia, hypertension, and dyslipidemia. Ferulic acid (FA) is one of the phenolic compounds that possess strong antioxidant property. The aim of this study was to investigate whether FA could attenuate the metabolic syndrome and oxidative stress induced by a high-carbohydrate, high-fat diet (HCHF) in rats. Method: Male Sprague Dawley rats (220-250 g) were randomly divided into three groups (n= 5-8/group). Rats in group 1 were fed with standard chow. Rats in groups 2 and 3 were fed with a HCHF diet with 15% fructose in drinking water, for 16 weeks. After receiving HCHF diet for 10 weeks, rats in group 3 were orally administered with FA (30 mg/kg/day) for the last 6 weeks of the treatment protocol. Result: Rats fed with HCHF diet showed the symptoms of MS, including hypertension, dyslipidemia, hyperglycemia and impaired glucose tolerance. FA at test dose significantly reduced blood pressure, fasting blood glucose and plasma triglyceride levels whereas plasma HDL-C level was increased when compared with the untreated MS rats (P<0.05). In addition, plasma malondialdehyde and vascular superoxide production were also decreased in MS rats treated with FA (P<0.05). Conclusion: These results suggest that FA treatment attenuated the symptoms of MS with most likely mechanisms being decreases in oxidative stress. Key words: Ferulic acid, High-fat, high-carbohydrate diet, Metabolic syndrome, Oxidative stress